Fullerene C60 for enhancing phytoremediation of urea plant wastewater by timber plants - Yavari, S. (Springer Verlag, 2018)
Phytoremediation has been applied as a promising and cost-effective technique for removing nutrient pollutants from wastewater. In this study, the effect of fullerene C60 was assessed on enhancing the phytoremediation efficiency of teak plants over a period of 1Â month. Teak plants were supplied with fullerene C60 (0, 25, or 50Â mgÂ Lâ1) and fed daily with two types of urea plant wastewater (with and without adding optimum ratio of phosphorus and potassium). The required volume of wastewater by the teak plants, nitrogen removal percentage, plant growth parameters (plant height, number of leaves, leaf surface area, and dry biomass), and nutrient content was recorded throughout the study. The results showed that addition of 25Â mgÂ Lâ1 fullerene C60 to urea plant wastewater could increase water uptake and nitrogen recovery of the teak plants. Plant growth and nutrient contents of teak plants were also increased in the presence of 25Â mgÂ Lâ1 fullerene C60. However, addition of 50Â mgÂ Lâ1 fullerene C60 to the wastewater decreased the values for water uptake and nitrogen recovery. The findings indicated that addition of proper amount of fullerene C60 to the teak-based remediation system can increase the efficiency of the plants for nitrogen removal. Â© 2018, Springer-Verlag GmbH Germany, part of Springer Nature.